Bridging climate change science and policy through TMNs in Turkey: CoM as a boundary-object - Erbil, Aslı Öğüt; Eroğlu, Mehmet; Türk, Ebru Gönül (Oxford University Press (OUP), 2022)
This paper qualitatively investigates one of the influential transnational municipal networks, Covenant of Mayors for Climate and Energy (CoM)’s position in three Turkish municipal governments in bridging the climate change science and climate change policy gap. In the last two decades, the importance of science-based policymaking for climate mitigation and adaptation and transnational municipal networks empowered by municipalities that guide city policies linked to international agreements has been recognized. In this paper, we argue that CoM has acted as a boundary-object in producing climate change policies and plans in Turkish municipal governments. However, CoM has done so to a certain extent; their effectiveness was limited due to the general atmosphere on climate change policies in Turkey. We substantiate this claim through a two-layer examination: a case-specific analysis of three municipalities and semi-structured interviews with thirteen experts in climate change policy-related issues.
Keywords: iklim değişiklikleri; public policy; belediye yönetimi; Covenant of Mayors for Climate and Energy; politika oluşturma; climatic changes; municipal government; policymaking; kamu politikası